Interdependence model in cross-disability friendships - Nurjaman, Tabah Aris; Faturochman, Faturochman (Universitas Ahmad Dahlan, 2025)
The visual limitations experienced by blind individuals necessitate the development of friendships with sighted individuals, who are perceived as available and willing to help. The provision of the aid indicates a dependency of blind individuals on their sighted counterparts. However, the development of friendship broadens the scope of interaction, thereby transforming the dependency pattern into a more dynamic relational spectrum, ranging from independent and dependent to interdependent forms. This study aims to explore models of interdependent manifestations in friendships between individuals who are blind and those who are sighted. A qualitative approach utilizing a descriptive phenomenological method was employed. Data collection involved in-depth interviews with six informants, all of whom were male students from inclusive universities. The interdependent relationship patterns in these friendships are manifested through three key components: joint activities, shared experiences, and social support, each with its own model. The coherence of activities includes accidental, interference, and pure models. Bilateral and unilateral models characterize shared experiences, while social support comprises communal, transactional, and proportional models.